Acceptance of protection technology in a time of fear: the case of Covid-19 exposure detection apps. Issue 3 (2nd July 2021) - Alsaad, Abdallah; Al-Okaily, Manaf
Abstract : Purpose: This study explores the acceptance of protection technology, namely, exposure detection apps, in the context of the Covid-19 pandemic. Unlike other situations, the context of the pandemic is characterized by large levels of threat and fear which largely affect the human decision-making process. To identify such characteristics, this study investigates the acceptance of exposure detection apps from the perspective of protection motivation theory (PMT). It examines how the perceived risk of Covid-19, perceived fear of Covid-19, self-efficacy, response efficacy and protection motivation interact to predict the acceptance of exposure detection apps. Design/methodology/approach: Data were collected from 306 Jordanian participants, and structural equation modelling was used for data analysis. Findings: The results reveal that acceptance of these apps is triggered by the perceived risk of Covid-19, which increases the experienced level of fear. The latter then initiates a compelling desire or motivation to protect oneself by using the recommended adaptive response (exposure detection app). The results show that an increased level of self-efficacy and perceived efficacy of exposure detection apps also contribute to the development of protection motivation and later the intent to use exposure detection apps. Originality/value: This study contributes to the technology acceptance domain by developing a context-driven model of the key characteristics of pandemics that lead to different patterns of technology acceptance. The key components in designing effective marketing campaigns to prompt the use of exposures detection apps are discussed.